PHITS Benchmarking for HPGe Detector Efficiency. (December 2017) - Peryoga, Yoga; Sagara, Hiroshi; Shiba, Tomooki
Abstract: Particle and Heavy Ion Transport code System (PHITS) validation for gamma-ray detector efficiency evaluation was performed. A coaxial type, 280 cm 3 high-purity Ge (HPGe) detector efficiency that was measured in previous experiments and calculated by Cyltran and MCNP was simulated by PHITS Ver. 2.82. The methodology and model on the previous works were carefully replicated to have a proper model of experimental apparatus and fair code comparison. Simulation was done by taking a single calculation for each energy line and setting the PHITS tally to simulate a pulse height detector. The energy cut-off was set low enough to accommodate the energy loss carried away by photons and electrons escaping from the active region of the detector, thus reducing the calculated efficiency into a more realistic result. Energy bin width in the tally was also set low to 0.2 keV, similar to the previous works. For the photon energy ranging from 40 keV to 1800 keV, PHITS calculation results show a fairly good agreement with experimental results, generally having discrepancies of less than 1%.